2020
DOI: 10.1038/s41550-020-1068-5
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities faced by women in access to permanent positions in astronomy in France

Abstract: We investigate inequalities in access to permanent positions in professional astronomy in France, focusing on the hiring stage. We use results from a national survey conducted on behalf of the French society of astronomy and astrophysics (SF2A) aimed at young astronomers holding a PhD obtained in France, and answered by over 300 researchers.We find that women are nearly two times less likely than men to be selected by the (national or local) committees attributing permanent positions (p = 0.06). We also find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We did not include doctorant in our analysis because of a small N. Chargé de recherche or researcher are generally hired by the CNRS and conduct research only and can advance to directeur positions of different grades. Meanwhile, maître de conferences are hired to both teach and research (Berné & Hilaire, 2020).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not include doctorant in our analysis because of a small N. Chargé de recherche or researcher are generally hired by the CNRS and conduct research only and can advance to directeur positions of different grades. Meanwhile, maître de conferences are hired to both teach and research (Berné & Hilaire, 2020).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We did not include doctorant in our analysis because of a small N. Chargé de recherche or researcher are generally hired by the CNRS and conduct research only and can advance to directeur positions of different grades. Meanwhile, maître de conferences are hired to both teach and research (Berné & Hilaire, 2020). Although this position can be termed as assistant professor, this is a permanent position (Berné & Hilaire, 2020), making it more akin to a tenured associate professor in the US context.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their statistics showed that women comprise 22 %-23 % of the permanent research personnel in the field in France, in line with the numbers from the PNP and IAU. Finally, a recent national survey on behalf of the French Society of Astronomy and Astrophysics suggests that at least two forms of bias, namely elitism and gender bias, exist in hiring in French astronomy (Berné and Hilaire, 2020).…”
Section: Women In the Fieldmentioning
confidence: 99%